2007
DOI: 10.1016/j.apmr.2007.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Criterion Validity of the StepWatch Activity Monitor as a Measure of Walking Activity in Patients After Stroke

Abstract: Criterion validity of the SAM to measure steps in both clinical and natural environments has been established when used on the nonparetic limb. However, more errors are apparent when the SAM is worn on the paretic limb while walking over a variety of outdoor terrains. Validation is recommended before use in patients with neurologic conditions affecting bilateral legs because there may be more error, particularly in outdoor activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(81 citation statements)
references
References 23 publications
(26 reference statements)
4
77
0
Order By: Relevance
“…It can be difficult for one reliability study to differentiate between this natural variation and measurement error. However, previous work has shown consistently that the StepWatch is accurate in step counting, 3,6,[12][13][14][15][16] so the variation detected in this study likely reflects true daily variation in activity levels. A potential source of error in the StepWatch is interpretation of certain activities such as cycling or leg swinging as steps.…”
Section: Discussionmentioning
confidence: 54%
“…It can be difficult for one reliability study to differentiate between this natural variation and measurement error. However, previous work has shown consistently that the StepWatch is accurate in step counting, 3,6,[12][13][14][15][16] so the variation detected in this study likely reflects true daily variation in activity levels. A potential source of error in the StepWatch is interpretation of certain activities such as cycling or leg swinging as steps.…”
Section: Discussionmentioning
confidence: 54%
“…Gait intensities were measured as gait cycles per minute. It has been shown that measurement of ambulatory activity using the SAM device was 99.87% accurate [19], and its validity has been proven [4,20]. The device has been used in several investigations in other medical applications [5-7, 9, 12, 27, 38], but has not previously been used to study degenerative spine diseases.…”
Section: Methodsmentioning
confidence: 99%
“…The studies which measured daily step counts reported they ranged as low as 1400 (Michael & Macko 2007) to 4000 (Fulk et al, 2010) steps per day. The exception was the study by Mudge et al, (2007) which found participants took an average of almost 6000 steps per day. Even so, compared to published norms of 6000 to 8500 steps per day for healthy older adults (TudorLocke & Myers 2001), these trials show that people after stroke are generally very inactive.…”
Section: What Are the Theoretical Underpinnings Of Group Circuit Clasmentioning
confidence: 99%
“…Of the trials that included mobility outcomes such as the Rivermead Mobility Index (Mead et al, 2007;Mudge et al, 2007) or the Elderly Mobility Scale (Mead et al, 2007), none showed significant improvements related to circuit class therapy. In the study of ) the degree of physical assistance required to walk was measured by the Iowa Level of Assistance Scale.…”
Section: Activities and Participationmentioning
confidence: 99%